Peptides and peptidomimetics in the p53/MDM2/MDM4 circuitry - a patent review. (1st December 2016) - Teveroni, Emanuela; Lucà, Rossella; Pellegrino, Marsha; Ciolli, Germana; Pontecorvi, Alfredo; Moretti, Fabiola
ABSTRACT: Introduction : Restoration of the p53 tumor suppressor function is an attractive anticancer strategy. Despite the development of several therapeutics targeting the two main p53 negative regulators, MDM2 and MDM4, no one has yet reached clinical application. In the past, several efforts have been employed to develop more specific and efficient compounds that can improve and/or overcome some of the features related to small molecule compounds (SMC). Peptides and peptidomimetics are emerging as attractive molecules given their increased selectivity, reduced toxicity and reduced tendency to develop tumor-resistance compared to SMC. Area c overed : This article reviews publications and patents (publicly available up to April 2016) for peptides and derivatives aimed to reactivate the oncosuppressive function of p53, with a particular focus on inhibitors of MDM2/MDM4. Emphasis is placed on the efficacy of these compounds compared to the p53-reactivating small molecules developed so far. Expert o pinion : A number of promising peptides for p53 reactivation in cancer therapy have been developed. These compounds appear to possess improved features compared to SMC, especially for their ability to simultaneously target the MDM2/MDM4 inhibitors, and their increased specificity.